The development of track two diplomacy in Indonesian led workshop on managing conflict in the South China Sea, 1990-2002 - Satyawan, lgnatius Agung (2015)
Conflict in the South China Sea became a flashpoint in Southeast Asia in the 1970s. Located in a strategic area which has important sea lanes and rich in living and non-living resources, the South China Sea is claimed by six states namely China, Taiwan, the Philippines, Vietnam, Malaysia and Brunei. However, in that period, there was no formal forum like the ASEAN Regional Forum (ARF) through which the conflict could be handled and as a result, Track Two Diplomacy was applied to manage the conflict through a series of meetings entitled “Workshop on Managing Potential Conflict in the South China Sea” led by Indonesia from 1990 to 2002. The statement of the problem of the thesis is why Track Two Diplomacy was chosen as a suitable mechanism to manage the conflict and to what extent was this experiment successful and effective. The objectives of the study are as follows: firstly, to examine the reasons for the deployment of Track Two Diplomacy as a mechanism of conflict management and Indonesian support for the workshop; secondly, to investigate the process, outcomes and effectiveness of the workshop. This research employs the qualitative method whereby a case study of the workshop is undertaken. Both primary and secondary data are analyzed. Theories used in this research are Constructivism which provides understanding on how socialization, identity and norms guide behaviour of states and Functionalism which stresses on promoting cooperation to enhance peace. The significance of this study is to suggest ways in which Track Two Diplomacy can be usefully deployed in managing conflicts in the South China Sea and elsewhere. The findings of this study are as follows: firstly, the interactive process of dialogue developed by the workshop has been able to create a sense of community and norms building. Secondly, the workshop succeeded to establish functional cooperation in less sensitive issues. Thirdly, the workshop further enhanced the concept of Track Two Diplomacy. Finally, the workshop was able to maintain peace in the region as indicated by absence of major military conflict since 1990